The griffin and Oliver Pie - Lawrence, Michael; Stower, Adam (London : Orchard Books, 2006)
"Oliver Pie is thrilled when he finds an ancient stone griffin under the weeds and ivy beyond the garden wall, but the griffin is crumbly and crochety. Once it was the proud Guardian of Hidden Treasure - now it is sad and neglected. But Oliver Pie is determined to become its friend."--Cover.
Keywords: Children's stories; Fiction